Initial Writing Learning from a Socio-Cultural Perspective: A Learning Experience on the Research Field - María Ivoneth Lozano Rodríguez (Enunciación, 2017)
In this article, the fundamentals of the training process of researchers on the Master in Pedagogy of the Mother Tongue context are explained. The reflection is oriented from projects that are developed in the first writing cycle. It presents the accompaniment process in the disciplinary, pedagogical, didactic and investigative field, starting from the teaching of writing problem in the first education. It starts from recognizing prescriptive and normative practices of language teaching in which writing is unknown as a social activity and the evolutionary process is not taken into account, nor a scaffolding that enhances what children already know favors their appropriation from social interaction and the granting of differentiated aid. In the same way, the article shows how, from the action research, transformative didactic proposals are being constructed, within the pedagogy by projects framework. That seek to correspond with the fundamentals of an interaction and sociocultural theory of learning and with a socio-discursive perspective of the acquisition of writing in which it is recognized as a fundamentally social, intentional, situated activity and its learning is constructed in interaction processes.